Role of TFEB and TFE3 in mediating lysosomal and mitochondrial adaptations to contractile activity in skeletal muscle myotubes - Ashley N. Oliveira; Yuki Tamura; Jonathan M. Memme; David A. Hood (Mitochondrial Communications, 2023)
Exercise is potent stimulus for mitochondrial adaptations, serving to activate mitochondrial biogenesis as well as mitochondrial turnover. Through the process of mitophagy, dysfunctional mitochondria are selectively targeted and recycled via the lysosomes, which is activated following a single bout of exercise. The microphthalamia (MiT) family of transcription factors, including TFEB and TFE3, are widely recognized as the master regulators of lysosomal biogenesis, as they homo- and hetero-dimerize to transcriptionally regulate lysosomal and macroautophagy-related genes. It is currently unknown to what extent TFEB and TFE3 regulate mitophagy, and whether these transcription factors mediate mitochondrial adaptations to contractile activity (CA). Here we show that following an acute bout of contractile activity in cultured C2C12 murine skeletal muscle myotubes, LC3-II mitophagy flux is induced and the absence of TFEB or TFE3 impairs this acute mitophagic response. However, the loss of either transcription factor alone does not mitigate the improvements in oxygen consumption seen following chronic contractile activity (CCA). Chronic contractile activity also elicited functional improvements in lysosomes including a reduction in size and increased proteolytic activity, evidenced by increased digestion and unquenching of DQ-BSA fluorophore, thereby illustrating a level of redundancy between the two transcription factors in mediating chronic contractile activity-induced adaptations. However, in the absence of both TFEB and TFE3, lysosomal adaptations were not observed following chronic contractile activity and subsequent mitochondrial adaptations were attenuated. These findings underscore the importance of the lysosomes, and of TFEB and TFE3, in mediating mitochondrial adaptations to chronic contractile activity.